Adverse drug reactions due to gabapentin-nortriptyline in patients with neuropathic pain in a tertiary care teaching hospital - Singh, Rohit Kumar; Kumar, Ujjwal; Kumar, Munish; Seth, Raj Narayan; Sinha, Rani Indira (International Journal of Basic & Clinical Pharmacology, 2022)
Gabapentin and Nortriptyline are used to treat neuropathic pain. Gabapentin belongs to a group of drugs called anti-convulsant and Nortriptyline belongs to tricyclic antidepressant. Gabapentin acts by binding to the specific site on voltage- gated calcium channels. This helps in relieving nerve pain and lowers the risk of seizure. Nortriptyline works by preventing the released chemical messengers in brain (serotonin and norepinephrine) from being reabsorbed back into the nerve cells. As a result, it prolongs the effect of serotonin and norepinephrine in the brain and over time, this helps to relieve depression and lighten the mood. We are reporting a case series including 3 patients having neuropathic pain and taking tablet gabapentin-nortriptyline in department of neurology, Patna medical college and hospital, Patna developed some adverse drug reactions. Causality assessment was done in each case by Naranjo scale. Each case was filled properly in ADR (adverse drug reaction) reporting form and was sent to nearby adverse drug reaction monitoring centre (AMC). During the posting for pharmacovigilance in neurology department of Patna medical college and hospital, Patna from 01/07/2022 to 30/09/2022 we got three adverse drug reactions due to gabapentin-nortriptyline. Two of them were due to Gabapentin and one was due to nortriptyline. Gabapentin-nortriptyline is one of the most commonly used drugs in neurology department. It causes some frequent as well as some rare adverse drug reactions which are required to be assessed and finally reported to the nearby AMC.